Mélnikov en París, 1925 - Sander Maurano (Slovo, 2013)
Mélnikov en París, 1925. By GINÉS GARRIDO. Pp. 262. Barcelona: Fundación Caja de Arquitectos. 2011. EUR32.00. Paperback. ISBN: 9788493785765. Click here to read the review.